2021
DOI: 10.3389/feduc.2021.737064
|View full text |Cite
|
Sign up to set email alerts
|

Are Social and Ethnic Reading Inequalities Increasing During School Closures?—The Mediating Role of Parental Involvement in Distance Learning

Abstract: From spring 2020 many countries throughout Europe and beyond temporarily closed schools to tackle the spread of the coronavirus. First studies indicate that these school closures resulted in lower learning gains compared to learning gains in preceding years and widened social and ethnic disparities by affecting disadvantaged students more strongly than their more advantaged peers. Moreover, during school closures, parental involvement in distance learning is regarded as crucial for successful learning, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…As a possible explanation for the additional support, the author of the study considered parents' additional free time due to unemployment (Green, 2020: p. 10). However, the associations are not always entirely clear; for example, Weber et al (2021) found an effect of social background on post-lockdown reading achievement for Austrian primary school students, but the results did not suggest that this difference was related to social differences in parental involvement. The issue of parental help with schoolwork was also addressed with data from the Dutch LISS panel (Bol, 2020), showing that highly educated parents provided more support with schoolwork during the COVID-19 pandemic than other parents and felt more capable of doing so.…”
Section: Educational Inequalities During the Covid-19 Pandemic And Th...mentioning
confidence: 81%
“…As a possible explanation for the additional support, the author of the study considered parents' additional free time due to unemployment (Green, 2020: p. 10). However, the associations are not always entirely clear; for example, Weber et al (2021) found an effect of social background on post-lockdown reading achievement for Austrian primary school students, but the results did not suggest that this difference was related to social differences in parental involvement. The issue of parental help with schoolwork was also addressed with data from the Dutch LISS panel (Bol, 2020), showing that highly educated parents provided more support with schoolwork during the COVID-19 pandemic than other parents and felt more capable of doing so.…”
Section: Educational Inequalities During the Covid-19 Pandemic And Th...mentioning
confidence: 81%
“…This greatly affects the learning interactions between teachers and students (Herwin et al, 2021;Pujiastuti et al, 2021). In this situation, parental involvement is a very crucial trigger for learning success (Weber et al, 2021). Parental involvement is very important in the learning process during the lockdown period and this has been shown to have the potential to improve children's social relationships, sense of self-esteem and self-efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The efforts of students and their families likely played a crucial role during school closures. Successful remote learning during the COVID-19 pandemic also depends on students' motivation and parental involvement (e.g., Weber et al, 2021).…”
Section: Practical Implicationsmentioning
confidence: 99%